Chronotype and quality of sleep in alpine skiers - Costa, M.; Re, M. (Chronobiology International, 2023)
Alpine skiing is among the most demanding sporting activities in terms of physical effort and mental workload. The aim of the study was to compare sleep quality and chronotype distribution between 84 highly trained alpine skiers and a control sample of 84 non-athletes matched by age and sex ratio. Quality of sleep was assessed by the Pittsburgh Quality of Sleep Index (PSQI), and chronotype was assessed by the Morningness-Eveningness Questionnaire (MEQ). Additional questions assessed sleep management during training or competitions. The results showed a marked skewed chronotype distribution towards morningness in alpine skiers (52.4% morning type, 42.8% intermediate, and 4.8% evening type) in comparison to the control group. The midpoint of sleep was significantly anticipated among alpine skiers. Differently from the previous literature that showed poor sleep quality and quantity in competitive athletes, the quality and quantity of sleep in alpine skiers was within the normal range in all the PSQI subcomponents.